A private library in the Age of Enlightenment: The library of The marquis de Montesa - Mendioroz Lacambra, Ana María (Huarte de San Juan. Geografía e Historia, 2009)
The main point of this work is to provideus with some data about the Enlightenedpanoramain the community of Navarra. For that,we have analyzed the funds of the Marquis ofMontesa’s library, cofounder of the Real SociedadTudelana de los Deseosos del Bien Público,one of the first Sociedades Económicas de Amigosdel País. This study not only approaches usto the owner’s ideology, but also helps us to knowthe spreading of the new school of thought of theIllustration in Navarra.
Keywords: Illustration; Navarre; marquis of Montesa; private library